Answer:
[tex]t = \frac{\sqrt{\omega0^2+2*\theta*\alpha} -\omega0}{\alpha}[/tex]
Explanation:
The rotated angle is given by:
[tex]\theta=\omega0*t+1/2*\alpha*t^2[/tex]
Since this is a quadratic equation it can be solved using:
[tex]x=\frac{-b \± \sqrt{b^2-4*a*c} }{2*a}[/tex]
Rewriting our equation:
[tex]1/2*\alpha*t^2+\omega0*t-\theta=0[/tex]
[tex]t = \frac{\±\sqrt{\omega0^2+2*\theta*\alpha} -\omega0}{\alpha}[/tex]
Since [tex]\sqrt{\omega0^2+2*\theta*\alpha} >\omega0[/tex] we discard the negative solution.
[tex]t = \frac{\sqrt{\omega0^2+2*\theta*\alpha} -\omega0}{\alpha}[/tex]